RANCANG BANGUN APLIKASI NILAI AKADEMIK SISWA BERBASIS WEB PADA SDN 98 PALEMBANG - Winda Rosadi Gultom; Nita Rosa Damayanti (JURNAL ILMIAH BETRIK, 2023)
As times progress, schools need to help improve the systems they implement, because computerized systems make it easier to process data. However, there are still many schools that still use manual methods such as SDN 98. Therefore, the data processing process takes quite a long time. The aim of this research is to design an application so that the resulting process is more efficient, fast and accurate to facilitate data processing operations and provide the latest information. This research uses a qualitative method with the waterfall system development method. With this application, it is hoped that it can help schools manage grades efficiently and effectively for good student grades. Research results have shown that the application of student academic scores can improve school quality and provide satisfaction to the community with the information provided.